2016
DOI: 10.1371/journal.pone.0165748
|View full text |Cite
|
Sign up to set email alerts
|

Development of PET Imaging to Visualize Activated Macrophages Accumulated in the Transplanted iPSc-Derived Cardiac Myocytes of Allogeneic Origin for Detecting the Immune Rejection of Allogeneic Cell Transplants in Mice

Abstract: Allogeneic transplantation (Tx) of induced pluripotent stem cells (iPSCs) is a promising tissue regeneration therapy. However, this inevitably induces macrophage-mediated immune response against the graft, limiting its therapeutic efficacy. Monitoring the magnitude of the immune response using imaging tools would be useful for prolonging graft survival and increasing the therapy longevity. Minimally invasive quantitative detection of activated macrophages by medical imaging technologies such as positron emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
0
18
1
Order By: Relevance
“…Luciferase-miPSCs (959A2-1-6) generated from C57BL/6 (B6) (CLEA) mouse embryonic fibroblasts were cultured in the absence of serum and feeder cells using ESGRO Complete PLUS Clonal Grade Medium (Millipore, Burlington, MA, USA). Cardiomyogenic differentiation of the iPSCs was performed as described, with modifications, followed by purification with glucose-free medium supplemented with lactic acid 22,23 ; iPSCs (3 × 10 3 ) were resuspended in 100-µl aliquots of differentiation medium [DM; Dulbecco's Modified Eagle's Medium (DMEM; Nacalai Tesque, Kyoto, Japan) containing 15% foetal bovine serum (FBS; Biofill, Melbourne, Victoria, Australia), 100 mmol/l non-essential amino acids (NEAA; Invitrogen, Carlsbad, CA, USA), 2 mmol/l L-glutamine (Invitrogen), and 0.1 mmol/l 2-mercaptoethanol (Invitrogen)] containing 0.2 mmol/l 6-bromoindirubin-3′-oxime (BIO; a glycogen synthase kinase-3β inhibitor to activate the Wnt-signalling pathway; Calbiochem, San Diego, CA, USA), and cultured in 96-well Corning Costar Ultra-Low attachment multiwell plates (MilliporeSigma, Burlington, MA) for 3 days. On day 3, an additional 100 µl of DM without BIO was added to each well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luciferase-miPSCs (959A2-1-6) generated from C57BL/6 (B6) (CLEA) mouse embryonic fibroblasts were cultured in the absence of serum and feeder cells using ESGRO Complete PLUS Clonal Grade Medium (Millipore, Burlington, MA, USA). Cardiomyogenic differentiation of the iPSCs was performed as described, with modifications, followed by purification with glucose-free medium supplemented with lactic acid 22,23 ; iPSCs (3 × 10 3 ) were resuspended in 100-µl aliquots of differentiation medium [DM; Dulbecco's Modified Eagle's Medium (DMEM; Nacalai Tesque, Kyoto, Japan) containing 15% foetal bovine serum (FBS; Biofill, Melbourne, Victoria, Australia), 100 mmol/l non-essential amino acids (NEAA; Invitrogen, Carlsbad, CA, USA), 2 mmol/l L-glutamine (Invitrogen), and 0.1 mmol/l 2-mercaptoethanol (Invitrogen)] containing 0.2 mmol/l 6-bromoindirubin-3′-oxime (BIO; a glycogen synthase kinase-3β inhibitor to activate the Wnt-signalling pathway; Calbiochem, San Diego, CA, USA), and cultured in 96-well Corning Costar Ultra-Low attachment multiwell plates (MilliporeSigma, Burlington, MA) for 3 days. On day 3, an additional 100 µl of DM without BIO was added to each well.…”
Section: Methodsmentioning
confidence: 99%
“…OCT4, NANOG, and LIN28, and using a previously reported protocol, they were differentiated into cardiomyocytes that expressed cardiomyocyte marker genes such as ANP-1, MYH7B, 1STL1, NKX2.5, MYH6, and TNNT2, with decreased OCT4, NANOG, and LIN28 expression ( Fig. 1a,b) [22][23][24] . Nearly all embryoid bodies exhibited self-beating at day 16 and the cells were positive for troponin T and alpha-actinin, indicating that they were iPSC-CMs (Fig.…”
Section: Differentiation Of Cardiomyocytes Derived From Ipscs Undiffmentioning
confidence: 99%
“…18 F-DPA-714 preparation was described in our previous publication ( Kashiyama et al, 2016 ). Accordingly, 18 F-fluoride in 18 O-H 2 O was transferred to a UG-M1 synthesiser (Universal Giken, Kanagawa, Japan) and passed through an Accell Light QMA cartridge.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, different strategies are adopted for cardiac regeneration using stem cell-derived CMs. Cells can then be injected as single cells, patches, or sheets [11,43,47,155,160,[197][198][199]. Almost all improved some metrics of cardiac function, suggesting paracrine factors excreted from grafts exert some regenerative capacity.…”
Section: Transplantation Of Ipsc-cms For Treatment Of Heart Failurementioning
confidence: 99%
“…Regardless of their maturity, researchers are currently studying the potential of iPSC-CMs for cardiac regeneration. Animal models such as rodents, canines, pigs, and primates are used [11,16,[41][42][43][44][45][46][47][48][49][50][51]. So far, some studies have shown encouraging results after iPSC-CM engraftment like long-term cell survival, increased cell maturation and contractile improvement while others have found the opposite.…”
Section: Introductionmentioning
confidence: 99%